An experimental study on the corrosion amount using a statistical analysis. (2nd January 2018) - Zhu, Hongjun; Liu, Xin; Jia, Chaolong; Du, Baisong; Liu, Simeng; Qian, Ying
ABSTRACT: A non-destructive estimation of the corrosion amount in the existing RC structure is highly desired and therefore this paper presents a proof-of-concept experimental demonstration of such a method, which is based on the eddy heat imaging (EHI) technique. Its basic principle is to convey a corrosion signal to the surface of RC structures by eddy heating. To develop the EHI method, the first key step is to address the question of whether the rate of change in surface temperature is strongly associated with the corrosion amount. In order to make the problem tractable, special equipment was designed, from which 81 observations were obtained for data analysis. After the statistical analysis of the observational data and preliminary application on an in-service bridge, the results show that the EHI method is a promising approach to the quantitative measurement of the corrosion amount of RC structures.